1998
DOI: 10.1001/archpsyc.55.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Euthymic Bipolar Patients With and Without Prior Alcohol Dependence

Abstract: Our findings support the presence of persistent neurocognitive difficulties in patients with long-standing bipolar disorder who are not in the psychiatrically acute state or who are suffering the effects of alcohol abuse and suggest that there may be an aggregate negative effect of lifetime duration of bipolar illness on memory and frontal or executive systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
291
3
35

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(367 citation statements)
references
References 33 publications
35
291
3
35
Order By: Relevance
“…The cognitive deficits in BD may be partially explained by abnormalities in functional brain structures and/or metabolism (Stoll et al, 2000;Manji et al, 2000;van Gorp et al, 1999;Coffman et al, 1990). As cognitive impairments are present in FH and persist during clinical remission in BD patients, they may be regarded as trait markers (Henry et al, 1973;van Gorp et al, 1998;Murphy et al, 1999;Coffman et al, 1990;Ferrier et al, 1999;Rubinsztein et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive deficits in BD may be partially explained by abnormalities in functional brain structures and/or metabolism (Stoll et al, 2000;Manji et al, 2000;van Gorp et al, 1999;Coffman et al, 1990). As cognitive impairments are present in FH and persist during clinical remission in BD patients, they may be regarded as trait markers (Henry et al, 1973;van Gorp et al, 1998;Murphy et al, 1999;Coffman et al, 1990;Ferrier et al, 1999;Rubinsztein et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Manic patients showed impairments on planning and reaction time (RT) (Murphy et al, 1999). During remission, cognitive deficits may persist (van Gorp et al, 1998;Ferrier et al, 1999;Rubinsztein et al, 2000;Scott et al, 2000); euthymic BD patients showed impairments on visuospatial recognition, verbal and nonverbal memory and learning, retrieval of information from semantic memory an increased RT on a planning task (Coffman et al, 1990;Ferrier et al, 1999;Rubinsztein et al, 2000). The fact that cognitive deficits persist during remission suggests that they constitute a trait marker in BD.…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with affective psychoses also have cognitive impairment, in these patients cognitive deficits are more strongly associated with clinical symptoms and state-related factors than they are in patients with schizophrenia (17,18). In a study of patients with schizophrenia or bipolar disorder who were assessed when psychotic at baseline and then 8 months later when remitted, only the bipolar patients improved in their cognitive performance (19); the patients with schizophrenia showed the same level of cognitive impairment at followup.…”
Section: Diagnostic Differences Regarding Relation Of Cognitive Impaimentioning
confidence: 99%
“…In fact, there is evidence that performance on cognitive tests declines as a function of past illness burden, 154,162,163 and that a past history of alcohol abuse can impact on cognitive performance in certain domains. 164 Neither the short-nor long-term impact of medication on cognitive performance is known, 165 and evidence is just emerging supporting a recurrent or even chronic dysregulation of HPA axis function in BD. 166,167 It is important, therefore, that potential cognitive endophenotypes be studied in unaffected family members of BD probands.…”
Section: Cognitive Endophenotypesmentioning
confidence: 99%